STRUKTUR KOMUNITAS PADANG LAMUN PULAU DERAWAN - Muhamad Roem; Asbar Laga (Jurnal Harpodon Borneo, 2014)
The aim of the research is to analize community structure derawan seagrass meadow. The research conducted in seagrass meadows of Derawan Island, East Kalimantan Province. The research method was ecological survey. Immensity and condition of the meadows were describe in decriptive analysis. The result of the research indicated that the ± 35 Ha seagrass of Derawan was dominated by H. Uninervis that made up to 86 % contribution to total relative density. H. Uninervis with average density 3.576 ± 115 ind m-2. Long term implication that confirmed this signs is the shifting in species composition for the last 18 years. There is an urgent of doing sea grass ecosystem rehabilitation to maintain the ecological sustainability of sea grass meadows as a habitat and sustainability of green sea turtle population as ecosystem user. Keywords : seagrass meadows, foraging habitat, green seaturtle, species shifting,  ecological sustainability.